Endobronchial intubation detected by insertion depth of endotracheal tube, bilateral auscultation, or observation of chest movements: randomised trial. (9th November 2010) - Sitzwohl, Christian; Langheinrich, Angelika; Schober, Andreas; Krafft, Peter; Sessler, Daniel I; Herkner, Harald; Gonano, Christopher; Weinstabl, Christian; Kettner, Stephan C
Abstract : Objective To determine which bedside method of detecting inadvertent endobronchial intubation in adults has the highest sensitivity and specificity. Design Prospective randomised blinded study. Setting Department of anaesthesia in tertiary academic hospital. Participants 160 consecutive patients (American Society of Anesthesiologists category I or II) aged 19-75 scheduled for elective gynaecological or urological surgery. Interventions Patients were randomly assigned to eight study groups. In four groups, an endotracheal tube was fibreoptically positioned 2.5-4.0 cm above the carina, whereas in the other four groups the tube was positioned in the right mainstem bronchus. The four groups differed in the bedside test used to verify the position of the endotracheal tube. To determine whether the tube was properly positioned in the trachea, in each patient first year residents and experienced anaesthetists were randomly assigned to independently perform bilateral auscultation of the chest (auscultation); observation and palpation of symmetrical chest movements (observation); estimation of the position of the tube by the insertion depth (tube depth); or a combination of all three (all three). Main outcome measures Correct and incorrect judgments of endotracheal tube position. Results 160 patients underwent 320 observations by experienced and inexperienced anaesthetists. First year residents missed endobronchial intubation by auscultation in 55% of cases and performed significantly worse than experienced anaesthetists with this bedside test (odds ratio 10.0, 95% confidence interval 1.4 to 434). With a sensitivity of 88% (95% confidence interval 75% to 100%) and 100%, respectively, tube depth and the three tests combined were significantly more sensitive for detecting endobronchial intubation than auscultation (65%, 49% to 81%) or observation(43%, 25% to 60%) (P<0.001). The four tested methods had the same specificity for ruling out endobronchial intubation (that is, confirming correct tracheal intubation). The average correct tube insertion depth was 21 cm in women and 23 cm in men. By inserting the tube to these distances, however, the distal tip of the tube was less than 2.5 cm away from the carina (the recommended safety distance, to prevent inadvertent endobronchial intubation with changes in the position of the head in intubated patients) in 20% (24/118) of women and 18% (7/42) of men. Therefore optimal tube insertion depth was considered to be 20 cm in women and 22 cm in men. Conclusion Less experienced clinicians should rely more on tube insertion depth than on auscultation to detect inadvertent endobronchial intubation. But even experienced physicians will benefit from inserting tubes to 20-21 cm in women and 22-23 cm in men, especially when high ambient noise precludes accurate auscultation (such as in emergency situations or helicopter transport). The highest sensitivity and specificity for ruling out endobronchial intubation, however, is achieved by combining tube depth, auscultation of the lungs, and observation of symmetrical chest movements. Trial registration NCT01232166 .